Potential for Social Conflicts Due to the Globalization of Digital Money - Kirana, Rininta Diang; Widodo, Pujo; Kusuma, Kusuma; sukendro, Achmed (Formosa Journal of Applied Sciences, 2024)
With the development of technology, digital money is spreading as a means of payment. The method used is qualitative descriptive. The results of the study show that The growth of social media and the adoption of cryptocurrencies marks a digital transformation in the payment system. However, the shift from cash to digital transactions has also had an impact. On the positive side, transactions are more practical and the risk of theft is reduced. However, there is a risk of system errors and potential social instability in the event of major disruptions in the digital system. The Great Reset agenda supports the use of digital money to improve economic efficiency and inclusivity, but it also poses challenges related to national sovereignty and security. Digital education, proper regulation, and international cooperation are key to effectively managing this complex transition.